4‐hydroxy tempo improves mitochondrial and neurobehavioral deficits in experimental model of Huntington's disease. Issue 3 (10th January 2015) - Sandhir, Rajat; Mahajan, Namita; Mehrotra, Arpit; Aggarwal, Aanchal; Sunkaria, Aditya
ABSTRACT Mitochondrial dysfunctions have been implicated in the progression of Huntington's disease (HD). To date, several free radical scavengers have been tested in experimental HD, but only a few have shown promise. Although most antioxidants rapidly reduce ROS but in the process they are oxidized, which limits their ability to protect. Therefore, in the present study we employed a potent recycling antioxidant, 4‐hydroxy tempo (4‐HT), because it can reinstate its reduced state even after its oxidation during scavenging of ROS. Female Wistar rats were administered 3‐nitropropionic acid (3‐NP) and/or 4‐HT for 21 days, after which animals were subjected to biochemical and behavioral assessments. Our results showed that 4‐HT treatment significantly attenuated the 3‐NP induced decrease in the activities of mitochondrial electron transport chain enzymes. In addition, 4‐HT administration restored the increased nitrite and lipid peroxidation levels. Apart from this, 4‐HT also attenuated the 3‐NP induced decrease in superoxide dismutase and catalase activities. Further, 4‐HT administration resulted in significant improvement in 3‐NP induced cognitive and motor impairments. Taken together, the results of the study demonstrate that 4‐HT is beneficial in 3‐NP induced model of HD and thus could be a potential therapeutic agent in management of this disease. Synapse 69:128–138, 2015. © 2014 Wiley Periodicals, Inc.